Strategi Pencegahan Pornografi dan Pornoaksi Berbasis Pendidikan Karakter Islam pada Remaja di Era Digital: Tinjauan Tafsir Ath-Thabari An-Nur Ayat 30-31 - Riski Amalia Nastiti (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to explore strategies for preventing pornography and indecency based on Islamic character education among adolescents in the digital era, through the interpretation of Ath-Thabari on Surah An-Nur verses 30–31. These verses provide a strong theological foundation for lowering the gaze (ghaddhul bashar), guarding chastity (hifzhul furuj), and covering the private parts as forms of self-protection from the negative influences of the digital environment. This research uses a qualitative approach with a library research method, with primary sources including the Qur’an and Tafsir Ath-Thabari, as well as secondary data from various relevant literature and journals. The results show that prevention strategies can be implemented through four main approaches: (1) Islamic character education in schools through strengthening strategies, persuasion, and normative re-education; (2) Education in the family environment using methods such as role modeling, habituation, storytelling, advice, and reward and punishment; (3) The role of society in forming Islamic social groups that actively address the influence of pornography; and (4) Strengthening individual Islamic character through faith, self-control, internet ethics, and repentance behavior. This study affirms that the interpretation of Ath-Thabari can provide applicable contributions in building a strong Islamic character education system as a moral safeguard for adolescents amid the overwhelming flow of digital information.